MORPHOLOGICAL FEATURES AND MECHANISM OF FORMATION OF DAMAGE TO THE STRUCTURES OF THE SPINE AND SPINAL CORD IN PERSONS OF MODERN CAR DRIVERS INJURED IN ROAD ACCIDENTS - Indiaminov Sayit Indiaminovich; Bakhtiyorov Bakhodir Bakhtiyorovich; Shopulatov Iskander Bakhtierovich (Web of Journals Publishing, 2024)
In the article, in order to identify the morphological features of the formation of spinal cord injuries (PSMP) The analysis of the results of the examination of corpses in relation to 119 drivers of modern Chevrolet- Daewoo- uz passenger cars was carried out for drivers of modern cars injured in an accident. those killed in an accident. The age of the drivers ranged from 18 to 59 years. It was found that the PSMP in drivers was most often characterized by tear-off fractures, mainly in the cervical region, respectively between C1-C2 or C5-C6, as well as in combination with tear-off fractures of the thoracic region. In some cases, such cervical and occipital injuries were observed. The nature of fractures of spinal structures in drivers indicates that tear-off fractures are the result of extensor-flexor movements of the spine at the time of an accident, and some compression and other types of spinal fractures were probably formed as a result of rotation or compression of the spine in the 1st and 2nd phases of an accident.